2018
DOI: 10.1007/s12192-018-0899-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-216b inhibits heat stress-induced cell apoptosis by targeting Fas in bovine mammary epithelial cells

Abstract: Heat stress affects milk yield and quality in lactating dairy cows in summer. Bovine mammary epithelial cells (bMECs) play a key role in milk secretion, and microRNAs (miRNAs) regulate numerous functions of bMEC. Previous reports have verified that miR-216b regulated cell apoptosis through repressing target genes in several cancer cells. So, our purpose was to explore the potential involvement of miR-216b in heat stress-induced cell apoptosis in bMECs. Firstly, the heat stress model was constructed and we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Cortisol is released from the adrenal cortex, which allows the body to continue to stay on high alert. Acutely, catabolic mechanisms of cortisol provide energy to the body [ 13 ]. The higher cortisol levels observed in HTHH group were in line with the higher heart rate in the corresponding group in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cortisol is released from the adrenal cortex, which allows the body to continue to stay on high alert. Acutely, catabolic mechanisms of cortisol provide energy to the body [ 13 ]. The higher cortisol levels observed in HTHH group were in line with the higher heart rate in the corresponding group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, microRNAs (miRNAs) was recognized as an important regulator of gene expression beyond the transcriptional stage and various biological reactions such as development, apoptosis, differentiation, and viral infection [ 12 ]. Additionally, miRNAs regulate numerous functions of bovine mammary epithelial cells (bMECs), which play a putative role in milk secretion [ 13 ]. In humans, it has been documented that miR-216 can regulate cell apoptosis through repressing target genes in several cancer cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress also reduces phagocytosis capacity and the oxidative burst of bovine PMN, which together with having the negative effect on the immune system may explain the increased susceptibility to IMI (Lecchi et al, 2016). Cai et al (2018) investigated apoptosis of bMECs under heat stress and found a differential expression of apoptotic genes and miRNAs which led to increased apoptosis. However, they also detected an antiapoptotic effect of miR-216b under heat stress in bMECs by targeting Fas.…”
Section: Effect Of Heat Stress On Bovine Mammary Epithelial Cells (Bmmentioning
confidence: 99%
“…Cai et al . (2018) investigated apoptosis of bMECs under heat stress and found a differential expression of apoptotic genes and miRNAs which led to increased apoptosis. However, they also detected an anti-apoptotic effect of miR-216b under heat stress in bMECs by targeting Fas.…”
Section: Effect Of Heat Stress On Mammary Pathophysiologymentioning
confidence: 99%